MiR-19a suppresses ferroptosis of colorectal cancer cells by targeting IREB2 - Hongwei Fan (Bioengineered, 2022)
Colorectal cancer (CRC) is the most common malignant tumor occurred in digestive system. However, the prognosis of CRC patients is poor. Therefore, it is urgent to illuminate the mechanism suppressing CRC and explore novel targets or therapies for CRC treatment. MicroRNAs (miRNAs) are a class of non-coding RNAs with a length of 20–23 nucleotides encoded by endogenous genes, which are associated with the development of a variety of cancers, including CRC. Studies have shown that miR-19a is identified as oncogenic miRNA and promotes the proliferation, migration and invasion of CRC cells. However, the relationship between miR-19a and ferroptosis in CRC remains unknown. Here, we reported that iron-responsive element-binding protein 2 (IREB2), as an inducer of ferroptosis, was negatively regulated by miR-19a. IREB2 is a direct target of miR-19a. In addition, ferroptosis was suppressed by miR-19a through inhibiting IREB2. Thus, we proposed a novel mechanism of ferroptosis mediated by miR-19a in CRC cells, which could give rise to a new strategy for the therapy of CRC.